The Insect Metaphor: Intrusion, Parasitism, and Transformation in Namwali Serpell's The Old Drift - Stefanova Radoulska, Svetlana (Research in African Literatures, 2023)
Literary insects have long attracted critical attention; however the poten-tial of the insect motif in postcolonial literature remains underexplored. This essay analyzes the insect metaphor and its relation to the concept of disruption in Namwali Serpell's The Old Drift (2019). First, I explore the itali-cized sections, asking how their insect narrator produces formal, linguistic, and acoustic disruption, immersing the reader in soundscapes that make audible previously unheard or silenced voices. I am also concerned with three insect-like phenomena: intrusion, parasitism, and metamorphosis in the context of three periods in the making of Zambia-colonialism and its immediate aftermath, the AIDS epidemic, and recent technological develop-ments. Analysis of the insect motif shows that imperfection, in its varying forms, is at the heart of disruption in Serpell's interconnected stories. From the desire to penetrate the secrets of otherness in "The Grandmothers" to embracing imperfection as a means of stirring up protests in children's revolutionary utopia, the author expresses her concerns about the inter-dependence between human, animal, and machine and warns the reader about the ethical implications of politically conditioned use of advanced technology.
Keywords: insect; intrusion; parasitism; WOS; Scopus